DJ MODEL: A MODEL OF SERVICE RECOVERY FOR STUDENT SATISFACTION USING DISTRIBUTIVE, INTERACTIONAL AND PROCEDURAL APPROACHES - Harsono, Soni; Widiantoro, Harry; ., Herizon (PEOPLE: International Journal of Social Sciences, 2015)
A failure in service will result in customer dissatisfaction. Unfortunately, not all unsatisfied consumers are willing to convey their complaints to the service provider concerned, but they switch to another service instead. This study is conducted at private universities in East Java, Indonesia which include Universitas, Institut, and Sekolah Tinggi with the category of Excellent, Favorite and Non-Favorite. To support the completeness of the data, this study involves 75-80 students per university. Purpuse of research: 1) the relationship and the effect of justice perceptions, with the dimensions of distributive justice (DJ), interactional justice (IJ) and procedural justice (PJ), on satisfaction, 2) the relationship and the effect of satisfaction on trust, word of mouth and loyalty, and 3) the relationship and the effect of the dimensions of distributive justice, interactional justice and procedural justice on trust, WOM and loyalty directly and indirectly mediated by satisfaction. The results show universities category of excellent, DJ has positive effect on student satisfaction at Universitas and Institut, but DJ has no effect on student satisfaction at Sekolah Tinggi. PJ has positive effect on student satisfaction at Universitas and Sekolah Tinggi, but PJ has no effect on student satisfaction at Institut. IJ has positive effect on student satisfaction at Sekolah Tinggi, but IJ has no effect on student satisfaction at universitas and institut. Universities with category of favorite, DJ has positive effect on student satisfaction at Universitas, Institut and Sekolah Tinggi. However, PJ has positive effect on student satisfaction at Institut only, while at Universitas and Sekolah Tinggi, PJ has no effect on student satisfaction. Universities with category of non-favorite, DJ has positive effect on student satisfaction at Universitas, Institut, and Sekolah Tinggi. However, PJ has positive effect on student satisfaction at Universitas only, while at Institut and Sekolah Tinggi, PJ has no effect on student satisfaction.